PHARMACOLOGIC ACTION OF SEVERAL EXTRACTS OF CIHUAPAHTLI - HIDALGO CHAVEZ, CONSUELO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
In mice CaCl2, MgSO4, and MgS2O3 injected intraven following or simultaneously with the admn of scorpion venom lessened the symptoms of intoxication and delayed death Ergotamine tartrate or atropine sulfate had no effect but when administered togethe
BOL INST ESTUD MED BIOL
Keywords: PHARMACOLOGIC, ACTION, EXTRACTS, CIHUAPAHTLI; CIENCIAS MEDICAS; FARMACOLOGIA; ANALISIS DE MEDICAMENTOS